Tafel analysis in practice - Li, D; Lin, C; Batchelor-Mcauley, C; Chen, L; Compton, R (Elsevier, 2018)

(untitled)
Voltammetric waves under five different mass-transport regimes (macroelectrode, microdisc, micro-hemisphere, micro-hemicylinder and single microband) for an irreversible one-electron transfer process were simulated and analysed to find the appropriate Tafel region for accurate analysis. The transfer coefficient was found to deviate significantly from its true value as a function of potential in all cases due to the influence of mass-transport. If and how a simple analytical mass-transport correction in which the current is corrected for the change in the reactant concentration at the surface can be used to improve the measurement of transfer coefficient was investigated. It is shown that this correction is only rigorously valid for a uniformly accessible microelectrode under a true steady-state condition. This translates to hemispherical electrodes only of the set of five considered. The fraction of the current used in Tafel analysis (Tafel region) can be increased to around 50% for quasi-steady state regimes (hemicylindrical and single band electrodes) with this analytical correction but it completely failed in linear diffusion regimes (macroelectrodes). In the latter case an improved empirical correction is suggested.